2013
DOI: 10.7307/ptt.v25i4.1210
|View full text |Cite
|
Sign up to set email alerts
|

Marine Accidents Researched Through Human Factor Prisma

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Technological developments and improved safety standards were expected to affirm overall human capacity and diminish the occurrence of human error (Turan et al, 2016). However, the statistics on maritime accidents has indicated that the system is not resilient to human errors (Ćorović and Djurović, 2013). For example, analyses have shown that human error has been the cause of 67 % of accidents reported to European Marine Casualty Information Platform (EMCIP) in period from 2011 till 2014 (EMSA, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Technological developments and improved safety standards were expected to affirm overall human capacity and diminish the occurrence of human error (Turan et al, 2016). However, the statistics on maritime accidents has indicated that the system is not resilient to human errors (Ćorović and Djurović, 2013). For example, analyses have shown that human error has been the cause of 67 % of accidents reported to European Marine Casualty Information Platform (EMCIP) in period from 2011 till 2014 (EMSA, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The present study also examined the occurrence of daily sleepiness. Higher results for daily sleepiness were found among pilots in comparison to professional groups with a higher risk of fatigue (e. g. truck and bus drivers or shift worker) [30][31][32]. Although significantly more pilots in 4-months ROS experienced psychological demands of the work, no difference was observed in the daily sleepiness between the employees of the two different ROS.…”
Section: Discussionmentioning
confidence: 78%
“…By design and effective implementation the ISM Code should support and encourage the development of safety culture in shipping [2,5].…”
Section: Ntroductionmentioning
confidence: 99%